2020
DOI: 10.1002/ardp.202000195
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of Osage orange (Maclura pomifera) leaf extracts

Abstract: The main goal of this study was to establish the chemical profile of Osage orange (Maclura pomifera) leaf extracts, obtained by conventional maceration technique, and to examine its antimicrobial activity. The identification and quantification of the extract compounds were done using ultra‐high‐performance liquid chromatography, with a diode array detector coupled with triple‐quadrupole mass spectrometer and gas chromatography–mass spectrometry techniques. Thirty‐one polyphenolic compounds were detected and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was concluded that two previously isolated isoflavones from this plant, osajin and pomiferin, are responsible for the antibacterial activity of the fruit extract (Mahmoud 1981). Filip et al (2021) demonstrated that Gram-positive bacteria are often more sensitive to extracts obtained from MP fruits compared to Gram-negative strains. The highest antimicrobial activity was highlighted against the species Listeria monocytogenes and Enterococcus faecalis (Filip et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that two previously isolated isoflavones from this plant, osajin and pomiferin, are responsible for the antibacterial activity of the fruit extract (Mahmoud 1981). Filip et al (2021) demonstrated that Gram-positive bacteria are often more sensitive to extracts obtained from MP fruits compared to Gram-negative strains. The highest antimicrobial activity was highlighted against the species Listeria monocytogenes and Enterococcus faecalis (Filip et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Various species of M. pomifera are used in traditional medicine worldwide, with the fruits and leaves being primarily utilized in this sense. Existing literature to date also describes the potential use of the tree's bark as a source of bioactive chemical compounds, albeit with limited data to verify this aspect (Filip et al 2021). In this context, the aim of this study was to assess the influence of different extraction methods on the chemical and biological properties of extracts obtained from the bark and periderm of M. pomifera.…”
Section: Introductionmentioning
confidence: 99%
“…Some chemical compounds such as thiosulfinates, organic acid, flavonoids, phenolics saponin, and glucosinolates can potentially replace synthetic chemical preservatives [ 128 ]. It is well known that the phenolic compounds in plants, such as aliphatic alcohols, isoflavonoids, ketones, acids, aldehydes, and terpenes, are the main component with antimicrobial properties [ 129 ]. The phenolic compounds act as reducing agents, donating hydrogen and suppressing oxygen, producing an antioxidant effect on the product.…”
Section: The Use Of Natural Products As Alternative Preservatives: Ho...mentioning
confidence: 99%
“…It has recently been the subject of research since it has been found to contain a high content of lipids and carbohydrates that can be used to produce biofuels, even with characteristics very similar to petroleum-derived fuels [58,62,63]. Additionally, the fruit, bark, leaves, root, and seed have been reported to have a high content of oils, sugars, and compounds such as isoflavones, xanthones, triterpenes, and stilbenes, with isoflavones being the most representative [15].…”
Section: Maclura Pomífera (Raf) Schneidmentioning
confidence: 99%
“…The species of this genus are a rich source of bioactive compounds, mainly flavonoids as the principal constituents [1,[10][11][12][13][14]. For example, Maclura pomífera, one of the most studied species, contains isoflavones in the fruits, root, bark, and heartwood of the plant [13][14][15][16][17]. The substantial presence of phenolic compounds within the bark and the occurrence of flavonoids and dibenzophenones within the leaves confer upon it a spectrum of beneficial attributes encompassing anti-inflammatory, antimicrobial, antioxidant, anticancer, and antiproliferative activities [1,13,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%